A new technique of quantifying protoporphyrin IX in microbial cells in seawater - Gu, Lide; Yue, Xinli; Zhong, Haowen; Mei, Kang; Wang, Deli (Frontiers in Marine Science, 2022)
Protoporphyrin IX (PPIX), a fundamental precursor in the synthesis of heme and chlorophyll, plays a vital role in the biological metabolism and biogeochemical cycling in the ocean. PPIX has previously been identified in humans, animals, and plants, while so far as we know, there is no measurements until now regarding its contents in microbes, and especially in marine phytoplankton and bacteria. Here, for the first time, we reported a method of determining PPIX in marine microbial cells via acetone extraction followed by reversed phase high-performance liquid chromatography quantification, in which acetone-acetonitrile/water-formic acid buffer was used as a gradient elution solvent. The method was optimized with the detection limit of 3.8 ± 1.0 pM, and recovery rate of 97.5 ± 1.9%). The structure of the extracted PPIX was further confirmed using tandem mass spectrometry as positively associated with specific protonated molecules [M + H]+. The method was then successfully applied in the determination of PPIX in microbial cells in the water samples collected from a median-sized subtropical estuary (the Jiulong River Estuary, China). The results showed that PPIX existed widely and ranged from 20 – 170 ng/L in cells in the water samples. In the whole estuary, cellular PPIX generally decreased linearly with increasing salinity. A positive correlation of PPIX with particulate organic matter in the estuary suggested of sediment suspension and dissolution as its possible source. In addition, a general hyperbolic fitting pattern was observed for PPIX against dissolved inorganic nitrogen, PO43-, and the bacterial abundance (104 – 106 cells/mL) in the estuary. Such results indicated that PPIX played a crucial role in linking nutrients and the microbial productivity. In summary, we developed a new technique of quantifying cellular PPIX in water samples and confirmed the wide existence of cellular PPIX in natural waters. The data from Jiulong River estuary further suggest that the contents of cellular PPIX be enhanced with the nutrient supply from riverine inputs and sediment suspensions, which thereafter dictate the productivity of phytoplankton and bacteria in coastal waters.